The impact of hepatic pressurization on liver shear wave speed estimates in constrained versus unconstrained conditions - Rotemberg, V; Palmeri, M; Nightingale, R; Rouze, N; Nightingale, K (Physics in medicine & biology, 2012)
Increased hepatic venous pressure can be observed in patients with advanced liver disease and congestive heart failure. This elevated portal pressure also leads to variation in acoustic radiation-force-derived shear wave-based liver stiffness estimates. These changes in stiffness metrics with hepatic interstitial pressure may confound stiffness-based predictions of liver fibrosis stage. The underlying mechanism for this observed stiffening behavior with pressurization is not well understood and is not explained with commonly used linear elastic mechanical models. An experiment was designed to determine whether the stiffness increase exhibited with hepatic pressurization results from a strain-dependent hyperelastic behavior. Six excised canine livers were subjected to variations in interstitial pressure through cannulation of the portal vein and closure of the hepatic artery and hepatic vein under constrained conditions (in which the liver was not free to expand) and unconstrained conditions. Radiation-force-derived shear wave speed estimates were obtained and correlated with pressure. Estimates of hepatic shear stiffness increased with changes in interstitial pressure over a physiologically relevant range of pressures (0-35 mmHg) from 1.5 to 3.5 m s−1. These increases were observed only under conditions in which the liver was free to expand while pressurized. This behavior is consistent with hyperelastic nonlinear material models that could be used in the future to explore methods for estimating hepatic interstitial pressure noninvasively.